Vasovagal Syncope in the older adult - O'Dwyer, Clodagh (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Medical Gerontology, 2013)
Vasovagal Syncope (VVS) is a common form of neurally mediated syncope which affects at least one third of the population at least once in their lifetime. Commonly referred to as a “simple faint” and often described as benign in nature, little is known surrounding VVS in older adults. Through the use of clinical assessments, this thesis aims to clarify if age- related differences exist with VVS.
Keywords: Medical Gerontology, Ph.D.; Ph.D. Trinity College Dublin